Phosphorus supplementation modulates nitric oxide biosynthesis and stabilizes the defence system to improve arsenic stress tolerance in mustard. (5th January 2021) - Khan, M. I. R.; Khan, N. A.; Jahan, B.; Goyal, V.; Hamid, J.; Khan, S.; Iqbal, N.; Alamri, S.; Siddiqui, M. H.
Abstract: The interaction of mineral nutrients with metals/metalloids and signalling molecules is well known. In the present study, we investigated the effect of phosphorus (P) in mitigation of arsenic (As) stress in mustard ( Brassica juncea L.). The study was conducted to investigate potential of 30 mg P·kg −1 soil P supplement (diammonium phosphate) to cope up with the adverse effects of As stress (24 mg As·kg −1 soil) in mustard plants Supplementation of P influenced nitric oxide (NO) generation, which up‐regulated proline metabolism, ascorbate–glutathione system and glyoxalase system and alleviated the effects of on photosynthesis and growth. Arsenic stress generated ROS and methylglyoxal content was scavenged through P‐mediated NO, and reduced As translocation from roots to leaves. The involvement of NO under P‐mediated alleviation of As stress was substantiated with the use of cPTIO (NO biosynthesis inhibitor) and SNP (NO inducer). The reversal of P effects on photosynthesis under As stress with the use of cPTIO emphasized the role of P‐mediated NO in mitigation of As stress and protection of photosynthesis The results suggested that P reversed As‐induced oxidative stress by modulation of NO formation, which regulated antioxidant machinery. Thus, P‐induced regulatory interaction between NO and reversal of As‐induced oxidative stress for the protection of photosynthesis may be suggested for sustainable crops. Abstract : Supplementation of phosphorous reversed arsenic‐induced oxidative stress and protected photosynthesis and growth inhibition.